The Utilization of Artificial Intelligence as a Contract Review Tool for Government Procurement of Goods and Services to Mitigate Legal Risks - Siswahyudi Siswahyudi; Suartini Suartini; Anis Rifai (Bina Nusantara University, 2025)
This study examines the application of Artificial Intelligence (AI), specifically Natural Language Processing (NLP), as a strategic tool in reviewing government procurement contracts to mitigate legal risks. Manual contract review processes are often inefficient, prone to human error, and unable to keep up with the volume and complexity of government contracts. Using a normative-judicial legal research method, the study analyzes how AI integration can enhance legal certainty, efficiency, and accountability in public procurement. Through document digitization, standardized contract formats, and audit trail systems, AI can identify ambiguous or risky clauses, verify compliance with regulations, and provide recommendations supported by legal data and precedents. The study also investigates the current legal framework in Indonesia, identifying gaps that hinder AI implementation in administrative practices. While the ITE Law and Presidential Regulations offer a foundation for digital systems in governance, there is still no specific regulation governing AI use in legal decision support. Comparative insights from the UK, US, EU, and Morocco show that AI has improved review accuracy, reduced processing time, and strengthened public sector integrity, although concerns over transparency and algorithmic accountability persist. The study concludes that the integration of AI into procurement contract management offers significant potential for bureaucratic reform and risk mitigation, but requires robust legal frameworks, clear boundaries of responsibility, and institutional readiness. With adaptive policy support, ethical oversight, and inter-agency collaboration, AI can serve as a transformative instrument for enhancing good governance, preventing legal disputes, and protecting public officials in the execution of procurement responsibilities.